"Doing Good" versus "Being Good": The interplay between pride appeals and regulatory‐focused messages in green advertising. Issue 11 (22nd August 2021) - Hong, Ji Mi; Lim, Rachel Esther; Atkinson, Lucy
Abstract: Many consumers feel proud of making green choices, which is of crucial relevance to explaining environmentally responsible behaviors. However, compared to other self‐conscious emotions, such as guilt and shame, little research attention has been paid to the role of pride in green consumerism. Through conducting two online experimental surveys, this research examined what features of a message induce the two facets of the emotion pride—authentic and hubristic—and how pride appeals interact with message frames having different regulatory foci. In Study 1, participants revealed more favorable eco‐friendly attitudes and intentions when hubristic pride appeals were combined with promotion‐focused messages (detailing the positive benefits of using the green product), and when authentic pride appeals were matched with prevention‐focused messages (emphasizing the negative consequences averted by using the green product). Study 2 replicated and supported the proposed matching hypotheses while including a control condition. Findings of this research will add to a growing body of literature on pride as a discrete emotion and its carryover effects on persuasion while providing guidelines to help practitioners design green advertising campaigns.